A magnetic isolation IGBT driver architecture with short circuit protection - Liu Jiajun; Li Fei; Chen Rongxin; Deng Yuqing; Xiao Peilei (Dianzi Jishu Yingyong)
A magnetic isolation IGBT drive architecture with short circuit protection is designed in this paper. The architecture adopts transformer isolation, integrates desaturation detection circuit, Miller clamp circuit and soft turn-off. When IGBT exits the saturation zone due to short circuit fault, soft turn-off is performed on the device. The gate voltage spike is suppressed by Miller clamp circuit. At the same time, the fault signal is fed back to the front controller through the fault feedback channel to realize the fast response to the short-circuit fault. The simulation and measured results show that the architecture has an isolated voltage withstand of 8 kV, desaturation detection and Miller clamp threshold of 9 V and 2 V respectively, desaturation fault response time of 419 ns, fault error time of 311 ns, soft shutdown time of 136 ns. The architecture realizes short-circuit fault protection and fault feedback, and has been applied to a high voltage isolated IGBT driver.